Squamous cell carcinoma arising in a skin graft donor site following melanoma extirpation at a distant site: A case report and review of the literature. (March 2015) - Kearney, L.; Dolan, R.T.; Parfrey, N.A.; Kelly, E.J.
Summary: The development of both squamous cell carcinoma (SCC) and keratoacanthoma (KA) in donor sites following split thickness skin graft harvest are rare complications reported in the literature. Management of such cases requires a precise distinction between keratoacanthoma and SCC and knowledge of the degree of differentiation. We describe the case of a 48-year-old male who developed a squamous cell carcinoma with features of KA within a donor site on his right thigh. This developed six weeks following split skin graft harvest to cover a defect on his right anterior chest following wide local excision of a 2.4 mm Breslow thickness superficial spreading melanoma. We review previous cases in the literature along with theories suggested for their development and conclude the development of SCC with features of KA in this reported case was likely a de novo lesion. This case highlights the need for evaluation of the donor site at all surveillance examinations of the primary tumor site and urgent diagnostic biopsy of all non-healing and new lesions.